One piece. East Blue. Vol. 3, Don't get fooled again - Oda, Eiichiro, 1975-; Amemiya, Naoko; Caselman, Lance (San Francisco, CA : VIZ Media, LLC, 2015)
Captain Kuro, the much-feared captain of the Black Cat Pirates, has been hiding out, posing as a butler until the time is right to launch an attack, and only Monkey D. Luffy and a band of amateur pirates stand in his way.
"East Blue" refers to the story arc covered in v. 1 through 12 of the One Piece series.
"First published in Japan in 1997 by Shueisha Inc, Tokyo"--Page facing t.p.
"Parental advisory. One Piece is rated T for teen and is recommended for ages 13 and up. This v. contains fantasy violence and tobacco usage"--Page facing t.p.
"This book reads from right to left"--Back cover.
"This v. contains material that was originally published in English in Shonen Jump #14-17"--Page facing t.p.
Translated from the Japanese.
Keywords: Pirates -- Comic books, strips, etc. -- Fiction; Treasure troves -- Comic books, strips, etc. -- Fiction; Buried treasure -- Comic books, strips, etc. -- Fiction; Manga; Pirates -- Comic books, strips, etc. -- Fiction; Action and adventure comics; Graphic novels